Generation and Comprehensive Analysis of Host Cell Interactome of the PA Protein of the Highly Pathogenic H5N1 Avian Influenza Virus in Mammalian Cells - Gao, Zhao; Hu, Jiao; Liang, Yanyan; Yang, Qian; Yan, Kun; Liu, Dong; Wang, Xiaoquan; Gu, Min; Liu, Xiaowen; Hu, Shunlin; Hu, Zenglei; Liu, Huimou; et al. (Frontiers in Microbiology, 2017)
Accumulating data have identified the important roles of PA protein in replication and pathogenicity of influenza A virus (IAV). Identification of host factors that interact with the PA protein may accelerate our understanding of IAV pathogenesis. In this study, using immunoprecipitation assay combined with liquid chromatography-tandem mass spectrometry, we identified 278 human cellular proteins that might interact with PA of H5N1 IAV. Gene Ontology annotation revealed that the identified proteins are highly associated with viral translation and replication. Further KEGG pathway analysis of the interactome profile highlighted cellular pathways associated with translation, infectious disease and signal transduction. In addition, Diseases and Functions analysis suggested that these cellular proteins are highly related with Organismal Injury and Abnormalities and Cell Death and Survival. Moreover, two cellular proteins (nucleolin and eukaryotic translation elongation factor 1-alpha 1) identified both in this study and others were further validated to interact with PA using co-immunoprecipitation and co-localization assays. Therefore, this study presented the interactome data of H5N1 IAV PA protein in human cells which may provide novel cellular target proteins for elucidating the potential molecular functions of PA in regulating the lifecycle of IAV in human cells.